Tatanan Keyakinan Masyarakat Sunda (Sunda Wiwitan) di Era 4.0 - Hisam Ahyani; Jagad Rayana; Ahmad Hapidin (Al-Tsaqafa : Jurnal Ilmiah Peradaban Islam, 2021)
The belief system in a society today in an all-digital era can be formed by itself, meaning that the trust of a society is formed naturally. Where the belief system is a way of life that is believed by a community in carrying out its socio-religious life. The Sundanese people as an ethnic group that still exists in Indonesia today have an interesting and unique original belief system, namely Sunda Wiwitan. Sunda wiwitan as a good teaching and can be practiced for the Islamic community, especially in Indonesia in the digital era like today (the era of disruption 4.0) is First, the Sundanese people as one of the second largest tribes in Indonesia after the Javanese, have a pattern and model of Religiosity which is high, interesting and unique which is relevant in the Sunda Wiwitan religion which is still being preserved in the Baduy indigenous peoples in Banten Province and West Java Province. Second, the pattern of religiosity offered by the Sunda Wiwitan community in the 4.0 era included polite attitudes and behavior, and servitude with the term "Sang Hyang Kersa" in the form of prose. Third, the pattern that is preserved in the religiosity that exists in Sunda Wiwitan, today in the 4.0 era (digital/disruption) is able to influence various aspects of people's lives that exist in the Sundanese, namely as is often practiced in social, religious, political, and development life. As a result, the current pattern of religiosity rather than Sundanese diversity in the 4.0 era is relevant, as evidenced by the many Sundanese people who are involved in the world of politics and development. In addition, the form of embodiment of god consciousness (not atheist), and cultural awareness (maintaining the cultural mandate of the Sundanese ancestors) is a real proof of the values of Sundanese wiwitan religiosity.